Perbandingan Pakan Cacing Sutra dengan Azolla terhadap Pertumbuhan Ikan Patin - Muhammad Sidik Darmawan A; Novita MZ; Arif Supendi (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
The catfish (Pangasius sp.) is a popular freshwater fish among consumers, both in Indonesia and internationally. One of the main challenges in catfish farming is the suboptimal use of feed. The commonly used feed consists of natural and artificial types. Natural feed is divided into two categories: animal-based and plant-based. The animal-based natural feed frequently used by farmers is tubifex worms. However, tubifex worms have a drawback, as their availability in the market is limited. Therefore, a study was conducted to explore the use of Azolla as an alternative feed for catfish. This study used a Completely Randomized Design (CRD) with one treatment and two levels, namely 100% Azolla and 100% tubifex worms. The study was conducted over a period of 14 days. The observed parameters included fish growth (length and weight), survival rate (SR), Feed Conversion Ratio (FCR), and water quality (temperature, pH, and dissolved oxygen). The data from the study were analyzed using a mean value test. The results showed that the use of Azolla as feed had a positive impact on catfish growth, although it was not yet effective in fully replacing 100% tubifex worms. There was an increase in biomass of 13.8 grams and an average length increase of 0.56 cm during the 14-day maintenance period.